Библиотеки и «многократная грамотность»: обсуждение проблем информационной грамотности на 75-й Генеральной конференции ИФЛА «Библиотеки создают будущее, основываясь на культурном наследии» (Милан, 2009) (Библиосфера)
It is shown that the problems of information literacy are of interest for specialists in foreign and domestic libraries and higher school, while in many countries it is understood in different ways. The work of the IFLA Standing Committee on Information Literacy to promote information education and enlightenment is described.